The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.12688/f1000research.52957.3
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of first-person accounts of noetic experiences

Abstract: The term “noetic” comes from the Greek word noēsis/noētikos that means inner wisdom, direct knowing, intuition, or implicit understanding. Strong cultural taboos exist about sharing these experiences. Thus, many may not feel comfortable transparently discussing or researching these topics, despite growing evidence that these experiences may be real. The study’s objective was to qualitatively evaluate first-hand accounts of noetic experiences. 521 English-speaking adults from around the world completed an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…As the first step to developing the NSI, we conducted a qualitative study with 521 English-speaking adults worldwide. The detailed results of this preliminary study are reported elsewhere ( Wahbeh et al, 2022 ). Participants who self-identified as having noetic experiences completed an online survey that collected demographic data and four open-ended questions about noetic experiences.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…As the first step to developing the NSI, we conducted a qualitative study with 521 English-speaking adults worldwide. The detailed results of this preliminary study are reported elsewhere ( Wahbeh et al, 2022 ). Participants who self-identified as having noetic experiences completed an online survey that collected demographic data and four open-ended questions about noetic experiences.…”
Section: Methodsmentioning
confidence: 98%
“…Ten most used subthemes were expressing to or sharing with others, impacting decision-making, intuition/“just knowing,” meditation/hypnosis, inner visions, setting intentions/getting into the “state,” healing others, writing for self, and inner voice. Using Dedoose web-based qualitative data analysis software (version 8.3.17, Dedoose, Inc., Hermosa Beach, CA), 78 codes were generated from this qualitative data set as reported in Wahbeh et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations